2020
DOI: 10.1186/s12905-020-01130-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in togolese women: immunohistochemistry subtypes

Abstract: Background Molecular classification of breast cancer is an important factor for prognostic and clinical outcomes. There are no data regarding molecular breast cancer subtypes among Togolese women. The objective of this study was to evaluate the expression of ER, PR, HER2, and molecular subtypes of breast cancer receptors in Togolese patients and to establish the correlation between clinical and histological data and molecular types. Methods Clinicopathologic data of patients were collected from clinical recor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
4
8
0
Order By: Relevance
“…Our findings of the distribution of the molecular subtypes correlate with the patterns found in the study by Dickens et al [ 2 ]; however, these prior studies, including our study, found that HER2-OE is the least common subtype in South Africa. Our study also agrees with international studies that have explored the trend of these subtypes [ 5 , 45 ]. With respect to the correlation between molecular subtype and age, our study corroborates with Dickens et al [ 2 ], which shows that the proportion of Luminal A increased with age and showed a decreasing pattern with Luminal B, as well as HER2-OE and TNBC at an older age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of the distribution of the molecular subtypes correlate with the patterns found in the study by Dickens et al [ 2 ]; however, these prior studies, including our study, found that HER2-OE is the least common subtype in South Africa. Our study also agrees with international studies that have explored the trend of these subtypes [ 5 , 45 ]. With respect to the correlation between molecular subtype and age, our study corroborates with Dickens et al [ 2 ], which shows that the proportion of Luminal A increased with age and showed a decreasing pattern with Luminal B, as well as HER2-OE and TNBC at an older age.…”
Section: Discussionsupporting
confidence: 92%
“…Breast cancer (BC) is a complex and heterogeneous disease and remains the most commonly diagnosed malignancy among women in South Africa [ 1 ]. The prognosis of this disease depends on several biological and clinical features, including oestrogen and progesterone (ER and PR) receptors, human epidermal growth factor (HER2) receptor, Ki67 proliferation index, histologic type, and tumour grade [ 2 5 ]. This histopathology information forms the basis for a patient's optimal treatment decisions, described in a pathology report.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis by Eng et al [24] reported that most cases of BC in Africa were positive for ER. As in our study, Adani-Ifè et al [25] found that the proportion of patients expressing ER (54.7%) was higher than that of PgR positive (41%). The same observation has been reported by different authors [18,[26][27][28].…”
Section: Discussionsupporting
confidence: 84%
“…BC subtypes were correlated with histological grade (p < 0:0001 ). A significant association between the histological grade and the molecular subtype of BC was also reported in Ivorian [18], Togolese [25], Moroccan [38], Sudanese, and Eritrean women [39].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation